ESDD Prediction of Outdoor Polymer Insulators - Khaled, Abdelrahman (2015)
A Master of Science thesis in Electrical Engineering by Abdelrahman Khaled entitled, "ESDD Prediction of Outdoor Polymer Insulators," submitted in June 2015. Thesis advisor is Dr. Ayman Hassan El-Hag and thesis co-advisor is Dr. Khaled Assaleh. Soft and hard copy available.